The Role of MicroRNAs in Arterial Stiffness and Arterial Calcification. An Update and Review of the Literature - Nanoudis, Sideris; Pikilidou, Maria; Yavropoulou, Maria; Zebekakis, Pantelis (Frontiers in Genetics, 2017)
Arterial stiffness is an independent risk factor for fatal and nonfatal cardiovascular events, such as systolic hypertension, coronary artery disease, stroke and heart failure. Moreover it reflects arterial aging which in many cases does not coincide with chronological aging, a fact that is in large attributed to genetic factors. In addition to genetic factors, microRNAs (miRNAs) seem to largely affect arterial aging either by advancing or by regressing arterial stiffness. MiRNAs are small RNA molecules, approximately 22 nucleotides long that can negatively control their target gene expression posttranscriptionally. Pathways that affect main components of stiffness such as fibrosis and calcification seem to be influenced by up or downregulation of specific miRNAs. Identification of this aberrant production of miRNAs can help identify epigenetic changes that can be therapeutic targets for prevention and treatment of vascular diseases. The present review summarizes the specific role of the so far discovered miRNAs that are involved in pathways of arterial stiffness.